Determinants of audit fees - Lau, Tong Hwee (2014)
Audit fee-setting is a subjective process in which different audit firms employ different criteria in billing clients. As such, it will be beneficial to remove uncertainties surrounding the fee-setting process. Our study hopes to achieve this by identifying the determinants of audit fees, and from there, develop a model of audit fee determinants.